2022
DOI: 10.1177/09691413221101807
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of the COVID-19 pandemic on breast cancer screening and diagnosis rates: A rapid review and meta-analysis

Abstract: Objective The ongoing COVID-19 pandemic has caused an indefinite delay to cancer screening programs worldwide. This study aims to explore the impact on breast cancer screening outcomes such as mammography and diagnosis rates. Methods We searched Ovid MEDLINE, Ovid Embase, medRxiv and bioRxiv between January 2020 to October 2021 to identify studies that reported on the rates of screening mammography and breast cancer diagnosis before and during the pandemic. The effects of ‘lockdown’ measures, age and ethnicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 62 publications
2
31
1
2
Order By: Relevance
“…Moreover, the OSNA method gave us a clear status of axillary diagnosis, even if, for this type of tumour, there is no indication, other than theoretical, for axillary dissection. Therefore, the OSNA procedure allowed the best use to be made of the operating spaces available, with several surgeries that can be performed in the same session [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the OSNA method gave us a clear status of axillary diagnosis, even if, for this type of tumour, there is no indication, other than theoretical, for axillary dissection. Therefore, the OSNA procedure allowed the best use to be made of the operating spaces available, with several surgeries that can be performed in the same session [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was a difference in the procedures carried out in Phase 2 (more mastectomies and fewer quadrantectomies). This was because patients did not have easy access to hospital facilities or faced delays [ 23 , 25 , 26 ]. Moreover, it was not possible to conduct screening, leading to disease progression [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Throughout most of the world, the mammography screening programmes were paused at the start of the pandemic. This led to marked reductions in breast cancer screening at the start of the pandemic in many other countries worldwide (2-6). In Denmark, the mammography screening programme continued throughout the pandemic and the situation in Denmark is therefore unique and few studies are comparable to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in Denmark the mammography screening programme continued -and invitations and reminders were sent out -throughout the pandemic since early detection of cancer was considered of high priority. Studies from other countries have shown marked reductions in breast cancer screening during the pandemic as a result of the temporary closures of the screening programmes (2)(3)(4)(5)(6); however, the participation in mammography screening in Denmark with a continuation of the programme has not yet been described.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, reviews showed that countries that implemented lockdowns measures showed the highest reduction in number of new cancer cases being diagnosed. Breast cancer diagnosis rates dropped by an estimate between 18-29% between 2019 and 2021 42 .…”
Section: Reduced Cancer Diagnosismentioning
confidence: 99%